2007
DOI: 10.1111/j.1365-2265.2007.02812.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in hydrocortisone plasma and saliva pharmacokinetics following intravenous and oral administration to Patients with adrenal insufficiency

Abstract: The wide interindividual variability in plasma and salivary profiles of cortisol following the administration of IV and oral hydrocortisone to patients with adrenal insufficiency and the poor correlation between salivary and plasma measurements suggest that salivary cortisol measurements cannot be used for individual hydrocortisone dosage adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 24 publications
4
44
1
Order By: Relevance
“…This is a feasible way of monitoring cortisol levels but some studies show wide inter-individual variability in plasma and salivary profiles of cortisol, and a poor correlation between salivary and plasma measurements has been shown in patients with adrenal insufficiency (80). In others, the correlation is far better and this approach used for monitoring (81).…”
Section: Difficulties With Monitoring Hc Replacementmentioning
confidence: 99%
“…This is a feasible way of monitoring cortisol levels but some studies show wide inter-individual variability in plasma and salivary profiles of cortisol, and a poor correlation between salivary and plasma measurements has been shown in patients with adrenal insufficiency (80). In others, the correlation is far better and this approach used for monitoring (81).…”
Section: Difficulties With Monitoring Hc Replacementmentioning
confidence: 99%
“…Serum cortisol peaks after taking HC, and then drops to lower than normal levels before the next dose; there is no night-time rise, so patients wake up with very low cortisol levels that contribute to early morning fatigue, a major drawback of current replacement regimes (3,18). Salivary cortisol assays have been suggested for assessing HC-based glucocorticoid replacement, but literature data differ in terms of its reliability (19,20,21,22). Cortisone acetate (CA) is an oral glucocorticoid that needs hepatic conversion to cortisol by the enzyme 11b-hydroxysteroid dehydrogenase type 1 (11b-HSD1).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that patients with an area under curve higher than the control 97.5th percentile showed no obvious signs of overdose [50]. Conversely, Thomson et al showed great variability in salivary cortisol in a crossover study of 27 patients being treated with hydrocortisone (oral or IV), and did not show a good correlation between plasma and saliva levels, making it difficult to employ in current practice [51]; • cortisol in hair: hair growth (1 cm per month) and the correlation between cortisol level in the hair and exposure to glucocorticoids could allow detection of overdose or underdosage in patients with adrenal insufficiency. A pilot study showed no significant difference between patients and female control subjects, but a difference was observed between male subjects [52]; • plasma ACTH: plasma ACTH does not assist in evaluating glucocorticoid replacement therapy with classic rapid release hydrocortisone since ACTH is always high in the morning on waking and then decreases rapidly after administration of hydrocortisone in primary adrenal insufficiency [53].…”
Section: Adult Patientsmentioning
confidence: 99%